The Trefftz finite elements modelling crack propagation - Sanecki, Henryk; Zieliński, Andrzej P. (Computer Assisted Methods in Engineering and Science; Vol 15 No 3-4 (2008), 2022)
Investigation of crack propagation can sometimes be a crucial stage of engineering analysis. The T–element method presented in this work is a convenient tool to deal with it. In general, T-elements are the Trefftz-type finite elements, which can model both continuous material and local cracks or inclusions. The authors propose a special T-element in a form of a pentagon with shape functions analytically modelling the vicinity of the crack tip. This relatively large finite element can be surrounded by even larger standard T-elements. This enables easy modification of the rough element grid while investigating the crack propagation. Numerical examples proved that the "moving pentagon" concept enables easy automatic generation of the T-element mesh, which facilitates observation of crack propagation even in very complicated structures with many possible crack initiators occurring for example in material fatigue phenomena.